2014
DOI: 10.1080/09603123.2014.915015
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte nuclear factor-4α, a multifunctional nuclear receptor associated with cardiovascular disease and cholesterol catabolism

Abstract: Cardiovascular diseases (CVDs), the leading cause of death worldwide, are associated with high plasma cholesterol levels. The conversion of cholesterol to bile acids (BAs) accounts for about 50% of total cholesterol elimination from the body. This phenomenon occurs in the liver and is regulated by nuclear receptors such as hepatocyte nuclear factor-4α (HNF-4α). Therefore, special emphasis is given to HNF-4α properties and its multifunctional role, particularly in the conversion of cholesterol to BAs. HNF-4α is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…HNF1A mutations cause maturity-onset diabetes of the young (MODY) type 3 (MODY3, OMIM #600496). The hepatocyte nuclear factor 4-alpha (HNF4A, Chr 20) is a regulator of CYP7A1 gene transcription among other genes [ 106 ]. HNF4A mutations cause MODY type 1 (MODY1, OMIM #125850).…”
Section: Genetics Of Ldl Cholesterol In the Big-data Eramentioning
confidence: 99%
“…HNF1A mutations cause maturity-onset diabetes of the young (MODY) type 3 (MODY3, OMIM #600496). The hepatocyte nuclear factor 4-alpha (HNF4A, Chr 20) is a regulator of CYP7A1 gene transcription among other genes [ 106 ]. HNF4A mutations cause MODY type 1 (MODY1, OMIM #125850).…”
Section: Genetics Of Ldl Cholesterol In the Big-data Eramentioning
confidence: 99%
“…HNF4α is a highly conserved member of the nuclear receptor superfamily of ligand-dependent transcription factors, acts as a homodimer and plays a critical role in early liver morphogenesis, fatal liver development, liver differentiation and metabolism by regulating the transcription of genes involved in each of these biological processes (5,(16)(17)(18). Numerous studies have also reported the central role of HNF4α in regulating a number of genes, such as cytochrome P450 genes (CYP2C8, CYP2C9, CYP2C19, CYP7A1, CYP3A4 and CYP8B1) that essential for the xenobiotic and drug metabolism, to protect individuals from toxic effects and provide key building blocks and nutrients to promote the growth or maintain the survival of the organism (5,(19)(20)(21). Due to its multiple functions, HNF4α is described as a master regulator in multiple signal channels.…”
Section: Introductionmentioning
confidence: 99%
“…9−12 HNF4A, known as an highly conserved transcription factor, highly regulates the conversion of cholesterol to bile acids and is therefore associated with cholesterol catabolism and cardiovascular disease. 13 HNF4A variants were identified to be susceptible to type 2 diabetes mellitus. 14,15 It was reported that HNF4A plays a key role in the regulation of drug metabolizing enzymes, such as UDP glucuronosyltransferase Family 1 Member A8, A9, and A10 (UGT1A8, -1A9, and -1A10).…”
Section: Introductionmentioning
confidence: 99%
“…The gene expression of UGTs can be controlled by nuclear receptors (NRs), such as hepatocyte nuclear factor 4α (HNF4A). HNF4A is a member of nuclear receptor superfamily and is highly expressed in liver and kidneys. HNF4A, known as an highly conserved transcription factor, highly regulates the conversion of cholesterol to bile acids and is therefore associated with cholesterol catabolism and cardiovascular disease . HNF4A variants were identified to be susceptible to type 2 diabetes mellitus. , It was reported that HNF4A plays a key role in the regulation of drug metabolizing enzymes, such as UDP glucuronosyltransferase Family 1 Member A8, A9, and A10 (UGT1A8, -1A9, and -1A10). , The specific disruption of HNF4A gene in mouse liver can obviously reduce liver UGT1A9 gene expression, and HNF4A was demonstrated to activate the UGT1A9 promoter …”
Section: Introductionmentioning
confidence: 99%